A Simple Model of Educational Standards - Costrell, Robert M. (American Economic Review, 1994)
I model standards for educational credentials, such as high-school diplomas. Standard-setters maximize their conception of social welfare, knowing that utility-maximizing students choose whether to meet the standard. I show that more egalitarian policymakers set lower standards, the median voter would prefer higher standards (under symmetric distributions), and decentralization lowers standards (among identical communities). Optimal standards do not necessarily fall with increased student preference for leisure, deterioration of nonstudent inputs to education, or increased student heterogeneity. Superseding binary credentials by perfect information increases average achievement and social welfare, for plausible degrees of heterogeneity, egalitarianism, and pooling under decentralization.